2017
DOI: 10.1101/102459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged exposure does not increase soil microbial community response to warming along geothermal gradients

Abstract: Predicting effects of climate change on ecosystem functioning requires knowledge of soil microbial community responses to warming. We used natural geothermal gradients (from +1°C to +19°C above ambient) in two subarctic grasslands to test the hypothesis that long-term exposure (>50 years) intensifies microbial community responses to warming compared to short-term exposure (5-7 years). Community profiles from amplicon sequencing of bacterial and fungal rRNA genes did not support this hypothesis: significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This occurred despite warming having no detectable influence over microbial community composition at the genus to operational taxonomic unit (OTU) level (i.e. OTU relative abundances; Supplementary Figs S3 & S4; ref 24). While it has been suggested that microbes acclimate to new thermal regimes9,22, we found no evidence to support this mechanism.…”
mentioning
confidence: 99%
“…This occurred despite warming having no detectable influence over microbial community composition at the genus to operational taxonomic unit (OTU) level (i.e. OTU relative abundances; Supplementary Figs S3 & S4; ref 24). While it has been suggested that microbes acclimate to new thermal regimes9,22, we found no evidence to support this mechanism.…”
mentioning
confidence: 99%
“…A final smaller group (13% of variables, 6 plant-related, 3 microbe-related, 8 soil properties) resisted 5-8 years, but not >50 years, of warming (Fig. 2c,f), and represented apparently buffered changes to some aspects of plant metabolism 30 , stoichiometry and growth, alongside lagged declines in the richness of plant and soil fungal communities 27 (Fig. 3c,f).…”
Section: Grouped Variables and Their Responses To Warmingmentioning
confidence: 99%
“…Although these variables were only a subset of those measured, they were responsible for eliciting the same warming response from the EOF of the full ecosystem. These variables included ephemeral increases in microbial activity 1 , plant phenology 26 and plant carbon to nitrogen ratios, temporary shifts in some aspects of soil fungal community composition 27 and attenuating losses of root, soil fungal and soil bacterial biomass (Fig. 3b,e).…”
Section: Grouped Variables and Their Responses To Warmingmentioning
confidence: 99%
See 2 more Smart Citations